Reflexiones en torno a la consideración pedagógica de la educación 'formal', 'no formal' e 'informal' - Jordán, José Antonio (Teoría de la Educación. Revista Interuniversitaria, 2009)
In this article, the author pretends -as already insinuates the proper title- to reflect upon the next points: a) the mutual relation between 'formal', 'no-formal' and 'informal' education; b) to question the proper concept of 'informal education'; c) to realize some epistemological considerations about the repercussions that the amplification of this object of knowledge can have on pedagogy, in its quality of science with a minimal proper entity; It's on these two last aspects of this article, that really falls the principal weigth or effort of this study.